2018
DOI: 10.1093/mnras/sty1030
|View full text |Cite
|
Sign up to set email alerts
|

An MAD explanation for the correlation between bulk Lorentz factor and minimum variability time-scale

Abstract: We offer an explanation for the correlation between the minimum variability timescale (MT S) in the prompt emission light curve of gamma-ray bursts (GRBs) and the estimated bulk Lorentz factor of these GRBs, in the context of a magnetically arrested disk (MAD) model. In particular, we show that previously derived limits on the maximum available energy per baryon in a Blandford-Znajek jet leads to a relationship between the characteristic MAD timescale, t M AD , in GRBs and the maximum bulk Lorentz factor: t M … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…And indeed active galactic nuclei (AGN), which in many ways can be considered scaled cousins of GRBs (e.g. Nemmen et al (2012); Zhang et al (2013); Wu et al (2016); Lloyd-Ronning et al (2018)), have truly distinct radio loud and quiet sub-populations (Wilson & Colbert 1995;Kellermann et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…And indeed active galactic nuclei (AGN), which in many ways can be considered scaled cousins of GRBs (e.g. Nemmen et al (2012); Zhang et al (2013); Wu et al (2016); Lloyd-Ronning et al (2018)), have truly distinct radio loud and quiet sub-populations (Wilson & Colbert 1995;Kellermann et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The BH-disk system has been shown to be a viable engine for the GRB jet, from the standpoint of the timescales and energetics involved (e.g., consider the energy available from a 20M star accreting 5M at a rate of .01 − 0.1M s −1 ; for more discussion on this, see, for example, Popham et al (1999)). Observationally, we see BH-accretion disks in active galactic nuclei (which can, in many ways, can be considered scaled cousins of GRBs; Nemmen et al (2012); Zhang et al (2013); Wu et al (2016); Lloyd-Ronning et al (2018)), and infer they are behind the relativistic jets observed in these objects.…”
Section: Introductionmentioning
confidence: 94%
“…In Lloyd-Ronning et al (2018), accretion rates of long GRBs were estimated in the context of the MAD model using…”
Section: Mad Disksmentioning
confidence: 99%
“…Correlation between Lorentz factor and minimum variability time scale. The minimum variability timescale, MTS, can be anti-correlated with the bulk Lorentz factor in the jet, if the magnetically arrested (MAD) flow is considered (Lloyd-Ronning et al 2018). However, in the MAD mode, the flux accumulated at the BH horizon, and the interchange instability rather than MRI governs the minimum timescale of variability.…”
Section: Variability Of the Jetmentioning
confidence: 99%